Transaminase Activity and Other Enzymatic Reactions Involving Pyruvate and Glutamate in Chlamydia (Psittacosis-Trachoma Group) - Weiss, Emilio (1967)
The agents of meningopneumonitis (MN) and of trachoma (TR) purified from chick embryo allantoic fluids and yolk sacs, respectively, were shown to produce CO(2) from the C(1) positions of pyruvate and glutamate, but not from the other carbon atoms. The reaction with pyruvate did not require did not require the addition of cofactors, but was stimulated to a small extent by α-lipoic acid and, in the case of TR, also by diphosphothiamine, and nicotinamide adenine dinucleotide (NAD). The reaction of MN with glutamate was greatly stimulated by the addition of NAD and pyruvate, and resulted in the accumulation of alanine. The reaction of TR with glutamate was also greatly enhanced by added NAD, but was not affected by added pyruvate. When eight intermediates of the citric acid cycle were added to MN cells incubated with glutamate-C(14), plus NAD and pyruvate, they reduced to varying degrees the evolution of C(14)O(2). It was shown by chromatography that the C(14) label extended to α-ketoglutarate and succinate, but not to fumarate and malate. A net gain in adenosine triphosphate could not be demonstrated in MN cells incubated with combined glutamate, pyruvate, oxaloacetate, and various cofactors. These results furnish additional examples of real or apparent gaps in enzyme sequences in Chlamydia.